2009
DOI: 10.1177/0898010108323302
|View full text |Cite
|
Sign up to set email alerts
|

Existential and Spiritual Needs in Mental Health Care

Abstract: This study illuminates how existential needs and spiritual needs are connected with health care ethics and individuals' mental health and well-being. The term existential needs is defined as the necessity of experiencing life as meaningful, whereas the term spiritual needs is defined as the need of deliverance from despair, guilt and/or sin, and of pastoral care. It discusses whether or not patients' needs are holistically addressed in Western health care systems that neglect patients' existential and spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
(56 reference statements)
0
32
0
2
Order By: Relevance
“…When these needs are identified, health care professionals and patients' relatives have the chance to react and support the patients in their struggle with chronic or fatal illness. Not meeting patients' needs means to ignore their dignity and fundamental rights, which "are now seen as core to health care ethics" [17]. A prerequisite for further research is having valid and reliable spiritual need assessment tools, which then must be implemented in well-designed health care studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When these needs are identified, health care professionals and patients' relatives have the chance to react and support the patients in their struggle with chronic or fatal illness. Not meeting patients' needs means to ignore their dignity and fundamental rights, which "are now seen as core to health care ethics" [17]. A prerequisite for further research is having valid and reliable spiritual need assessment tools, which then must be implemented in well-designed health care studies.…”
Section: Discussionmentioning
confidence: 99%
“…Molzahn and Sheilds found that nurses' reluctance to address spirituality involved "not having the right words, lack of education, a view that spiritual care is someone else's responsibility, influences of secularism and diversity in society, and the current health-care context" [39]. However, Koslander et al [17] argued that "if a patient´s existential and spiritual needs, like physical needs, are seen as resources that are to be taken into consideration in health care, then a holistic care approach can be developed". Puchalski clearly pointed to the fact that "by creating an atmosphere of caring compassion and a willingness to be open to whatever concerns the patient, the interaction becomes focused in a patient-centered model of care" [9].…”
Section: Addressing Spiritual Needs As An Approach In Health Carementioning
confidence: 99%
See 2 more Smart Citations
“…Such needs can be specifically religious, but even people who have no religious faith or are not members of an organized religion have belief systems that give their lives meaning and purpose". Other researchers (20,23,24) defined as spiritual needs "need for peace of mind", the "need of overcoming despair and guilt", and "to find meaning and purpose in life" as existential needs. Taylor stated (4,25) that the most important spiritual needs included being positive, loving others, finding meaning, and relating to God among patients with cancer and family caregivers.…”
Section: Dıscussıonmentioning
confidence: 99%